Offline Programming for Robotic Deburring Process of Aluminium Wheels - Bílek, Ondřej; Samek, David; Knedlová, Jana (Manufacturing Technology Journal, 2013)
The paper presents application of Siemens RobotExpert software of industrial robot offline programming. The deburring process of aluminium wheel is described and developed. The robotic work-cell contains robot ABB IRB 1600id and two axes positioner ABB IRBP A 750 D 1000 H 700. The final robot tool path is checked using the collision viewer, the joint status monitor, the tool centre point speed viewer and tracker.
Keywords: Deburring; RobotExpert; Aluminium; Offline Programming; Wheels